The Impact of Teachers' Emotional Support on Academic Grit Among Junior High School Students in Kupang City - Maksimilianus Mari; Lolang Maria Masi; I Putu Agus Apriliana (Indonesian Journal of Counseling and Development, 2026)
Junior high school students confront diverse academic challenges, including examinations, unsatisfactory academic performance, and increasingly demanding curriculum requirements. In navigating these obstacles, academic grit serves as a vital psychological characteristic that enables students to maintain persistence. This study examines the influence of teachers’ emotional support on students’ academic grit among public junior high school students in Kupang City. Employing a quantitative approach with a causal research design, the study involved 316 students selected via proportional stratified random sampling. Data were gathered using the Teacher Emotional Support Scale and the Academic Grit Scale, and subsequently analyzed through simple linear regression using SPSS version 22. The results indicate that teachers’ emotional support exerts a significant positive influence on students’ academic grit (p < 0.05). Specifically, teachers’ emotional support accounts for 29.5% of the variance in academic grit, while the remaining 70.5% is explained by factors outside the scope of this investigation. These findings underscore the critical role that supportive teacher-student interactions play in cultivating perseverance, tenacity, and resilience in academic activities. From a practical perspective, these results suggest that guidance counselors and subject teachers should strengthen emotionally supportive interactions and enhance the classroom environment to foster students’ academic grit and improve their capacity to cope with academic challenges.